CURRICULAR PROGRAM STATUS OF THE MECHANICAL AND ELECTRICAL ENGINEERING COLLEGES OF CEBU TECHNOLOGICAL UNIVERSITY IN THE LICENSURE EXAMINATION - Flores Jr., Januario L (Journal of Agriculture and Technology Management, 2015)
The performance of an institution in the licensure examination is a measure of the quality of the curricular program in developing the core competencies of students. Thus, this study aimed to evaluate the quality of the Engineering Programs of Cebu Technological University through the performance of the graduates in the licensure examination in comparison with the national passing percentage as reference standard. It also aimed to benchmark its performance with the top four private universities in Cebu offering engineering programs. The data used in this study were obtained from the Professional Regulation Commission from school year 2005 to 2012. Results of the study showed that there is no significant difference between the performance in the licensure examinations of the Mechanical and the Electrical Engineering of Cebu Technological University with that of the national passing percentage performance. Similarly, there is no significant difference between the performance of the two engineering programs of Cebu Technological University with the performance of the top four private universities in Cebu offering Mechanical and Electrical Engineering programs. It can be concluded that the performance of Cebu Technological University Engineering Programs in the licensure examinations was within the prescribed national standard, and at par with the performances of the top four private engineering universities in Cebu. It implies that the two programs of the Engineering Department of Cebu Technological University had produced graduates that are also equipped with the required competencies along with the graduates from other universities that are offering engineering courses in the place.